Genetic and Phenotypic Features of 2 Northern Italy Families with Dowling-Degos Disease Type 4 - Dario Tomasini; Carlo F. Tomasini; Andrea Michelerio; Eloisa Arbustini; Fabio Sirchia; Alrun Hotz; Judith Fischer; Svenja Rademacher (JID Innovations)
Dowling-Degos disease (DDD) is an autosomal dominant genodermatosis involving the folds with lentiginous hyperpigmentation and reddish–brown papules. Four main types of DDD with variable clinical presentations likely related to the heterogeneity of the gene variant landscape have been implicated. Pathogenic keratin 5 gene K5 gene variants favor a reticular distribution with predominant fold involvement, whereas pathogenic variants in POGLUT1 lead to a widespread form with acantholytic features previously named Galli–Galli disease, now belonging to the disease spectrum of DDD and renamed DDD type 4. This study details the clinical and histopathological features associated with the sequence variant c.205C>T, p.(Arg69∗) in POGLUT1 of 2 families from northern Italy affected by DDD4. Despite sharing the same variant, clinical manifestations varied among the affected members of the 2 families. Environmental factors probably contributed to phenotypic variability and symptoms exacerbation. Histopathology was sustained by digitiform rete ridges, suprabasal acantholysis, and dyskeratosis. Moreover, we detected aberrant keratin 5 gene K5 expression in 2 biopsies. A review of the literature on POGLUT1-related DDD subtypes contextualizes these findings. The fact that several patients have been reported to carry the variant c.205C>T, p.(Arg69∗) might point to a potential mutational hotspot.